2012
DOI: 10.1002/jcp.24056
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow stromal cells stimulate an angiogenic program that requires endothelial MT1‐MMP

Abstract: Bone marrow-derived stromal/stem cells (BMSCs) have recently been characterized as mediators of tissue regeneration after injury. In addition to preventing fibrosis at the wound site, BMSCs elicit an angiogenic response within the fibrin matrix. The mechanistic interactions between BMSCs and invading endothelial cells (ECs) during this process are not fully understood. Using a three-dimensional, fibrin-based angiogenesis model, we sought to investigate the proteolytic mechanisms by which BMSCs promote vessel m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 51 publications
3
46
0
Order By: Relevance
“…47 A final possibility relates to the influence of stromal cell identity on the proteolytic remodeling of the ECM during the neovascularization process. 24,48 Our published data suggest that capillary formation induced by fibroblasts is very fast (perhaps tumor-like), resulting from a plasmin-mediated proteolysis that rapidly degrades the matrix and disrupts its mechanical properties in a global fashion. By contrast, BMSCs and AdSCs induce a much more focal, strategic matrix remodeling that is MT1-MMP dependent and results in capillaries that form more slowly, but also in a more stable manner.…”
Section: Grainger Et Almentioning
confidence: 97%
“…47 A final possibility relates to the influence of stromal cell identity on the proteolytic remodeling of the ECM during the neovascularization process. 24,48 Our published data suggest that capillary formation induced by fibroblasts is very fast (perhaps tumor-like), resulting from a plasmin-mediated proteolysis that rapidly degrades the matrix and disrupts its mechanical properties in a global fashion. By contrast, BMSCs and AdSCs induce a much more focal, strategic matrix remodeling that is MT1-MMP dependent and results in capillaries that form more slowly, but also in a more stable manner.…”
Section: Grainger Et Almentioning
confidence: 97%
“…Clinical studies have revealed that MMP-14 overexpression is associated with poor prognoses in patients with various malignant tumors. [75][76][77][78] However, the mechanisms underlying MMP-14 expression in tumors remain largely uncharacterized. Of note, MMP-14 expression has been reported to be associated with microRNAs in pancreatic cancer, neuroblastoma, and glioma.…”
Section: Microrna-mediated Gelatinase Regulationmentioning
confidence: 99%
“…21,22 It is also known to induce ASC activity in vitro and in vivo. 23,24 In addition, it is commonly used in vascular tissue engineering due to its inherent angiogenic activity.…”
Section: Introductionmentioning
confidence: 99%